Whole-genome sequencing shows modulation of neurodegenerative genes by Withania somnifera in human SK-N-SH cells - Eshita Sharma; Eshita Sharma; Dilip Mehta; Dilip Mehta; Nikita Jadhav; Gunjan Gujrati; Gunjan Gujrati; S. Dhananya; Manju Moorthy; Gopalakrishna Ramaswamy; Yundong Zhou; Sujit Nair; et al. (Frontiers in Molecular Neuroscience, 2025)
BackgroundAging is driven by several primary and secondary hallmarks that manifest with age, of which neurodegenerative diseases are important manifestations. The ability to decelerate or reverse aging, and promote healthy aging, has garnered great interest in recent times. In traditional medicine, Withania somnifera (WS) or Ashwagandha has been recognized for its adaptogenic and rejuvenative effects.MethodsTo investigate WS-modulated global gene expression profiles, we performed whole-genome sequencing of WS-treated human neuroblastoma SK-N-SH cells at different doses (50 and 100 μg/mL) and time points (3 h and 9 h) and validation by quantitative real-time PCR (qRT-PCR) and immunoblotting. Disease enrichment analysis for brain-related disorders was performed by DisGeNET.ResultsUsing differential gene expression analyses, we identified 19,945 WS-modulated genes. Of these, 2,403 and 177 genes were significantly (p ≤ 0.05) upregulated and downregulated, respectively, by WS treatment. Interestingly, different patterns of gene expression were exhibited in dose-dependent (9 upregulated, 1 downregulated, 100 μg/mL 3 h vs. 50 μg/mL 3 h; 21 upregulated, 86 downregulated, 100 μg/mL 9 h vs. 50 μg/mL 9 h) and temporal kinetics (210 upregulated, 6 downregulated, 50 μg/mL 9 h vs. 50 μg/mL 3 h; 8 upregulated, 49 downregulated, 100 μg/mL 9 h vs. 100 μg/mL 3 h). Furthermore, qRT-PCR experiments validated the RNA-seq results. WS-modulated genes were implicated in Alzheimer’s disease, migraine, Parkinson’s disease, bipolar disorder, cognition, stress, anxiety, forgetfulness, sleep disorders, and substance abuse among others.ConclusionTaken together, our transcriptomic profiling study revealed for the first time that WS may modulate key genes in neurodegenerative disorders with potential beneficial implications for brain-related disorders and healthy aging.